1998
DOI: 10.1002/(sici)1097-4547(19980901)53:5<569::aid-jnr7>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal differentiation of chromaffin cells in vitro, induced by extremely low frequency magnetic fields or nerve growth factor: A histological and ultrastructural comparative study

Abstract: The application of nerve growth factor (NGF) to primary adrenal medulla chromaffin cell cultures induces phenotypic changes characterized mainly by the presence of neurites. A similar effect has been seen when these cells are stimulated by extremely low frequency magnetic fields (ELFMF). In this study, newborn rat chromaffin cells were cultured and subjected to NGF or ELFMF in order to compare their histological and ultrastructural characteristics. Cells cultured in the presence of NGF developed cytoplasmic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0
3

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(7 citation statements)
references
References 19 publications
0
4
0
3
Order By: Relevance
“…The daily exposure time was selected on the basis of previous reports demonstrating in vivo neuronal differentiation of chromaffin cells (Drucker‐Colín et al . 1994; Feria‐Velasco et al . 1998).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The daily exposure time was selected on the basis of previous reports demonstrating in vivo neuronal differentiation of chromaffin cells (Drucker‐Colín et al . 1994; Feria‐Velasco et al . 1998).…”
Section: Methodsmentioning
confidence: 99%
“…1999). In addition, different studies have demonstrated that an extremely low frequency magnetic field (60 Hz, 0.7 mT) induces cell differentiation and increases neurofilaments and neurite growth (Feria‐Velasco et al . 1998; Verdugo‐Díaz et al .…”
mentioning
confidence: 99%
“…Similarly, stimulation of cells with MF frequencies apart from the active frequency windows has been shown to act as an inhibitor to prestimulated Ca 2ϩ signaling (87,95). A variety of other MF-induced physiological effects indirectly suggests the involvement of the Ca 2ϩ signal pathway (20,37,55,68,72,76,80,96,98).…”
Section: Physiological Effects Of Mf Exposurementioning
confidence: 98%
“…Auch neuronale Differenzierungsprozesse konnten nachgewiesen werden. Feld-exponierte chromaffine Zellen entwickelten histologische und ultrastrukturelle Merkmale ähnlich denen nach NGF-Behandlung [6]. An Dorsalganglion-Explantaten von Rattenembryonen konnte gezeigt werden, dass pulsierende Magnetfelder das Auswachsen von Neuriten stimulieren [12], jedoch nur in Gegenwart von NGF.…”
Section: Psoriasis Und Camp (Zyklisches Adenosin Monophosphat)unclassified